Effect of Cytoflavin on Early Postanesthetic Recovery of Cancer Patients - K. F. Fatullayeva; A. U. Nurov; A. I. Saltanov (Общая реаниматология)
Objective: to evaluate the effect of the metabolic antihypoxant cytoflavin on the course of early postanesthetic recovery in patients operated on for various cancers. Subjects and methods: Fifty-seven patients aged 30 to 65 years, operated on for gynecological cancer, were examined. The patients were divided into 2 groups: 1) 28 patients who took cytoflavin and 2) 29 who did not. At the end of an operation, the agent was intravenously injected in a dose of 10 ml in a mixture with an equal volume of 0.9% sodium chloride solution. Thiopental sodium was used for initial anesthesia; arduan was employed to maintain muscle relaxation. Neuroleptic analgesia with fentanyl and droperidol or ataralgesia (fentanyl + relanium) was applied in both groups. The levels of hemoglobin, glucose, sodium, potassium, calcium, malonic dialdehyde (MDA) (Andreyev’s test), antioxidative activity (AOA) (Semenov’s test) were measured to evaluate the functional state of patients. The rating system for determining the recovery of consciousness, respiration, and motor activity, proposed by Aldret and Kroulik [8], and Bidway’s psychological testing, blood oxygen saturation and cardiac performance monitoring (TRITON, Russia) and some others were used to evaluate the efficacy of the drug in the early postanesthetic period. The results were statistically processed using Microsoft Excel and a package of Biostatistics 6.0. Results. The use of cytoflavin at the end of surgery has been established to have a beneficial effect on the early recovery period. This is manifested as shorter recovery of consciousness and respiration mainly in the ataralgesia group; fair oxygen saturation, lower MDA concentrations and higher AOA are revealed. Conclusion. Cytoflavin significantly reduces the recovery of consciousness and adequate respiration and the incidence of the fever, muscle tremor syndrome and fails to favor the occurrence of hypoglycemia. Inclusion of cytoflavin into a complex of anesthetic measures ensures metabolic correction, by enhancing the antioxidative activity of plasma and lowering the concentration of incomplete oxidation products (MDA). Key words: cytoflavin, succinic acid, gynecological cancer, early postanesthetic recovery.